Getting in Touch With Reality: An English Curriculum to Boost Students' Critical Thinking Skills and Interest in Global Issues - Clelia Pineda Báez; Astrid Núñez Pardo (Asociación Colombiana de Profesores de Ingles, 2016)
English teachers very often face experiences that cause high levels of frustration and anxiety that are the result of poorly planned curricula, limited and rigorous methodology, and lack of student involvement. However, this frustration and anxiety could be used as a platform to generate new ideas for the improvement of any English program. Our experience with students from various schools in the Universidad Externado de Colombia can be singled out as appropriate examples to illustrate how apparent negative input can be used to obtain positive outcomes.